(untitled) (Khwopa Journal, 2026)
This paper ponders upon George Orwell’s Animal Farm through the critical lens of Althusser and Plato’s allegory of the cave to portray the subtleness of oppression. Traditionally, the readings of the novella have so far focused on the criticism of the totalitarian regime and the betrayal of revolution, but the focal point of this study circles around the subtleness of oppression and the inability of animals to differentiate between liberation and manipulation. With the help of Althusser, the study dissects the tools that are used by the authority to input oppression into the system without anyone noticing it. And by using Plato’s allegory of the cave, the study discloses the illusion people carry from the habit and situation they grow in. Then, this study moves on to the manipulation of knowledge and memory itself with the help of subtle threat and subtle illusion. With this, we capture the value of the vulnerable time after the revolution; we capture the unseen chaos after the revolution that could turn the short relief into a new form of misery if not checked properly. And we also capture the difficulty in seeing these sights and acknowledging them before it is too late to fight back.